Выживаемость облученных клеток млекопитающих и репарация ДНК - Пелевина И. И. Ирина Ивановна; Саенко А. С. Александр Семенович; Готлиб В. Я. Валентина Яковлевна; Сынзыныс Б. И. Борис Иванович (Москва, Энергоатомиздат, 1985)
Авт. указаны на обороте тит. л.